Automotive Transmission Gearbox Synchronizer Sintered Hub Design. (January 2020) - Barathiraja, K; Devaradjane, G; Bhattacharya, Anup; Sivakumar, V; Yadav, Vivek
Highlights: Study of wear phenomena of the sinter hub teeth flank and the hub face. Study of sinter hardened & sintering with induction harden material surface load capacity. Study of crack propagation path for the teeth crack and the strut slot crack. FEA methodology of frontloading to capture the failure in the design phase. Abstract: Sintered hubs are typically used in automotive transmission gearbox synchronizer due to its near net shape. Sintered hubs have complex design due to their functional and packaging requirements. The required hardness and density are obtained using different grades of sintered powders, sintering temperature and the press load capacity. Many sintering materials with good mechanical properties are available with or without secondary heat treatment. However, there are concerns of sintered hub failure in the vehicle validation or during the intended service of the vehicle. This paper describes the design of automotive gearbox synchronizer sintered hub to meet the endurance life of the gearbox. The sintered hub wear on the synchronizer hub face and tooth flank are studied experimentally in the gearbox rig level test. This study is done for materials such as medium carbon sinter-hardened PM grade, sintered high carbon diffusion alloyed PM grade and sintered high carbon diffusion alloyed PM grade along with induction hardening process. The different gearbox loading conditions cause wear up to 70 µm on the synchronizer hubs. The hub to gear interface as well as hub tooth to sleeve tooth interface contact pressures and wear are studied based on the test results. The amount of hub digging is proportional to the applied load and the test duration. The medium carbon sinter-hardened material can withstand less pressure and less time when compared with the high carbon diffusion alloyed material with induction hardening. The design considerations to avoid hub digging and or material changes with process changes are analyzed. This paper also describes prediction methodology in FEA for the failure modes of synchronizer hub spline tooth crack and strut detent slot crack. The physical validation shows good trend matching correlation with the high-fidelity approach in CAE.